Pengaruh Good Corporate Governance, Company Size, BOPO, Leverage Terhadap Kinerja Keuangan Perusahaan Kimia di BEI (2017 – 2021) - Evi wulandari; Emmelia Tan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this study is to determine and assess the impact of Good Corporate Governance (Institutional Ownership, Board of Directors, Independent Board of Commissioners), Company Size, BOPO, and Leverage on the financial performance of chemical companies listed on the IDX (2017 – 2021). Secondary data are used in this investigation. All 20 chemical manufacturing enterprises on the IDX make up the study's population. Purposive sampling is the sample methodology employed. Ten businesses can be used as research samples since they match the requirements. Multiple linear regression analysis employing panel data and the Eviews 12.0 analysis tool is the analytic technique employed. According to the study's findings, institutional ownership has no discernible impact on financial performance, neither does the board of directors, the independent board of commissioners, company size, BOPO, or leverage.